2017
DOI: 10.4103/npmj.npmj_33_17
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of predonation screening for transfusion transmissible infections using rapid test kits in a hospital-based blood transfusion centre

Abstract: This analysis demonstrated that with proper donor selection, rapid screening for hepatitis B virus only before ELISA screening is more cost-effective. This will also reduce the waiting time for donors and counselling if HIV positive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The program was found to be highly cost-effective, with an ICER of US$540 per DALY averted compared to status quo where no publicly provided HBV screening or treatment was available. Integrating low-cost HBV POCs into existed healthcare services such as antenatal screening [ 52 , 58 , 107 ], blood donor screening [ 62 ] and HIV clinics [ 59 , 60 , 61 ] can be another solution to achieve scale-up of HBV testing [ 108 , 109 ]. Zhang et al [ 109 ] showed the integration of HBV screening within the existing antenatal care in Cambodia was highly cost-effective.…”
Section: Cost-effectiveness Of Using Pocs For Hepatitis Bmentioning
confidence: 99%
“…The program was found to be highly cost-effective, with an ICER of US$540 per DALY averted compared to status quo where no publicly provided HBV screening or treatment was available. Integrating low-cost HBV POCs into existed healthcare services such as antenatal screening [ 52 , 58 , 107 ], blood donor screening [ 62 ] and HIV clinics [ 59 , 60 , 61 ] can be another solution to achieve scale-up of HBV testing [ 108 , 109 ]. Zhang et al [ 109 ] showed the integration of HBV screening within the existing antenatal care in Cambodia was highly cost-effective.…”
Section: Cost-effectiveness Of Using Pocs For Hepatitis Bmentioning
confidence: 99%
“…[53][54][55] Secondly, financial constraints and the cost of blood transfusion are some of the reasons in the literature to explain why there is a lack of predonation screening for the DENV. 56,57 As shown in this review, very minimal research activities were observed in the African region regardless of the presence of dengue on the continent. A similar observation has also been made in a limited number of epidemiological research activities on the continent.…”
Section: Global Distributions Of Research Work Around the Dengue Viru...mentioning
confidence: 87%
“…In summary, despite that good cost effectiveness of PDT is reported in high transfusion‐transmissible infection (TTI) prevalence settings in Africa [31], the cost effectiveness in low HIV prevalence settings is still to be assessed. Moreover, stigmatization after HIV donor notification immediately after the donor testing may limit the acceptability of the PDT by benevolent donors and impact on regular blood donation.…”
Section: Discussionmentioning
confidence: 99%